Desenvolvimento de ferramenta de verificação de projetos básicos submetidos à secretaria do verde e meio ambiente da cidade de São Paulo - Scaramai, Micaelle da Paixão Barbosa (2023)
The lack of quality management in public projects leads to works with extended costs and deadlines. Given this scenario, it is important to understand the quality management process of basic projects in the public sector. For this purpose, a methodology is presented and evaluated in this research to improve the quality management of the basic projects contracted by the Department of Nature and Environment of the City of São Paulo (SVMA), in order to avoid unnecessary work and for a better standardization of analyses, aiming at the efficient use of public resources in contracting projects and works. With this purpose, exploratory qualitative research was developed, and the Action Research methodology was used, since the researchers and collaborators of the aforementioned department were actively involved in solving the problem. Furthermore, an FMEA analysis (Failure Mode and Effect Analysis) was conducted to fulfill the research objectives and understand the effectiveness of the tool. The use of the developed and evaluated tool in this research contributed to the standardization of analysis actions regarding the projects, ensuring quality in the processes and compliance with the items of the terms of reference published by SVMA, making the analysis of the projects more objective and reducing unnecessary work and the return of projects. As for the results achieved with the research, it was identified that it is necessary to continue using the checklist and applying the FMEA periodically, in order to help the SVMA department to maintain the flow of continuous improvement of the project quality management process, a scenario that is evidenced for the satisfactory improvements in its second application cycle. The application of FMEA in the tool has a direct impact on the financial return of companies and organizations, and this process is due to the minimization and elimination of potential failures in production processes, bringing significant gains to its application. Finally, it is suggested that new studies be carried out due to the lack of information regarding the state-of-the-art of the subject related to the public field.